MINI REVIEW: BLACK RICE (Oryza sativa L. Indica) AS POTENTIAL FOOD FOR ANTIHYPERGLYCAEMIC - Arifah Sri Wahyuni; Diski Wahyu Wijayanto (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
In Indonesia, rice (Oryza sativa L.) has different colors and shapes, visible from the plants and rice. There are several types of rice, one of which is black rice (Oryza sativa L. indica). Researchers are motivated to explore the benefits of black rice in Indonesia. This interest stems from the potential health benefits of black rice, such as its benefits in treating diabetes mellitus. The effectiveness of reducing blood sugar levels is crucial in the context of the increasing prevalence of diabetes in Indonesia, as projected by the International Diabetes Federation for 2045. The author made observations on the phytochemical and pharmacological activities of black rice, aiming to lay the foundation for further study and development. By searching online journals in the Scopus and PubMed databases using the keywords (“Black Rice”) AND (antidiabetic) OR (diabetes) OR (“glucose lowering”) for the last 10 years, the filtering process produced 3 articles on Scopus and 5 articles on PubMed, providing accurate data for review. Results show that black rice contains bioactive compounds such as flavonoids, phytic acid, polyphenolic compounds, and oryzanol, which provide significant health benefits. Anthocyanins, the main compounds responsible for the color of rice, contribute to antihyperglycemic properties and have various pharmacological activities, one of which is anti-diabetic benefits. In addition, the high content of anthocyanins, fiber, and other nutrients in black rice makes it effective in managing the glycemic index, and blood glucose levels, and improving overall health ...